2020
DOI: 10.1093/cercor/bhaa054
|View full text |Cite
|
Sign up to set email alerts
|

Top–Down Inhibitory Mechanisms Underlying Auditory–Motor Integration for Voice Control: Evidence by TMS

Abstract: The dorsolateral prefrontal cortex (DLPFC) has been implicated in auditory–motor integration for accurate control of vocal production, but its precise role in this feedback-based process remains largely unknown. To this end, the present event-related potential study applied a transcranial magnetic stimulation (TMS) protocol, continuous theta-burst stimulation (c-TBS), to disrupt cortical activity in the left DLPFC as young adults vocalized vowel sounds while hearing their voice unexpectedly shifted upwards in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 89 publications
6
25
0
Order By: Relevance
“…On the language domain, one study reports that neither cTBS nor iTBS over the left DLPFC influenced language switching (LS) control (Pestalozzi et al, 2020 ). However, in one study, cTBS over the left DLPFC led to increased vocal compensation for pitch perturbations, which was electro-physiologically accompanied by a reduction in P2 cortical responses (Liu et al, 2020 ). These results on the effects of TBS over DLPFC on language regulation attract diverse arguments, where on the one hand, DLPFC does not regulate language switching, and on the other, it exerts a top-down control over voice production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the language domain, one study reports that neither cTBS nor iTBS over the left DLPFC influenced language switching (LS) control (Pestalozzi et al, 2020 ). However, in one study, cTBS over the left DLPFC led to increased vocal compensation for pitch perturbations, which was electro-physiologically accompanied by a reduction in P2 cortical responses (Liu et al, 2020 ). These results on the effects of TBS over DLPFC on language regulation attract diverse arguments, where on the one hand, DLPFC does not regulate language switching, and on the other, it exerts a top-down control over voice production.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is evident that the left DLPFC modulates speech. The cTBS over the left DLPFC not only led to increased vocal compensation for pitch perturbation, but was also responsible for the reduction in cortical responses (Liu et al, 2020 ). This implies that the left DLPFC exerts a top-down inhibitory control on vocal production in response to auditory feedback, which was diminished after cTBS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown an association between reduced vocal compensations for pitch perturbations and increased P2 amplitudes in healthy populations following working memory training (Guo et al, 2017) and in individuals with PD following external auditory cueing (Huang et al, 2019). Moreover, one recent TMS study reported that disrupting activity in the left DLPFC by continuous theta-burst stimulation (c-TBS) led to enhanced vocal compensations for pitch perturbations that were accompanied by reduced P2 responses (Liu et al, 2020). Consistently, reduced high-gamma activity in the DLPFC was predictive of abnormally enhanced vocal compensations for pitch perturbations in patients with AD (Ranasinghe et al, 2019).…”
Section: Potential Mechanisms Of Efficacy Of Lsvt Loudmentioning
confidence: 99%
“…In addition, recent source localization work has shown the contribution of the prefrontal cortex to the generation of P2 responses to pitch perturbations (Huang et al, 2016;Guo et al, 2017). It is thus suggested that a top-down inhibitory mechanism mediated by the prefrontal cortex may underlie auditory-motor control of vocal production, preventing vocal motor behaviors from being excessively influenced by auditory feedback (Liu et al, 2020). In light of this idea, individuals with PD may be impaired in this top-down mechanism such that auditory feedback errors cannot be correctly perceived and appropriately corrected, resulting in their abnormally enhanced vocal compensations.…”
Section: Potential Mechanisms Of Efficacy Of Lsvt Loudmentioning
confidence: 99%
See 1 more Smart Citation